DEVELOPMENT OF AN E-CANTEEN SYSTEM WITH EXTREME PROGRAMMING TO OPTIMIZE EFFICIENCY, TRANSPARENCY, AND ACCOUNTABILITY IN CANTEEN MANAGEMENT AT THE FACULTY OF ENGINEERING, MATARAM UNIVERSITY - Murpratiwi, Santi Ika; Al Qadri, Ramadhani; Widiartha, Ida Bagus Ketut; Irmawati, Budi; Afwani, Royana; Agitha, Nadiyasari; Rassy, Regania Pasca (Informatika, Universitas Jenderal Soedirman, 2024)
The e-Canteen system enhances efficiency and user experience in electronic-based canteen services. The study aimed to develop a platform streamlining transactions, inventory management, and interaction between customers and canteen service providers. Before implementation, critical issues identified included manual inventory management and slow ordering processes, which created inefficiencies. The system allows customers to order, pay, and track stock availability online, leading to a more efficient and convenient purchasing process. For canteen service providers, automated inventory management helps optimize stock control and reduces manual errors, promising a more streamlined and error-free operation. The E-Canteen system offers significant benefits to both customers and service providers. Customers enjoy a more efficient and convenient purchasing process, while service providers benefit from optimized stock control and reduced manual errors, fostering a more productive and error-free work environment. Additionally, BLU Unram can monitor canteen performance, enabling data-driven decisions to improve services and policies. The system was developed using the Extreme Programming (XP) method, which ensured a user-centered design and rapid adaptation to feedback. Findings from the study demonstrated a 30% improvement in operational efficiency, with user satisfaction significantly increased according to internal surveys. The E-Canteen system addresses the operational challenges of managing canteen services and integrates smoothly with modern technological advancements, providing a scalable and adaptive solution for future growth. This system effectively resolves issues in traditional canteen management, offering benefits to customers and service providers regarding efficiency, convenience, and service quality.